The Reality of Student Teacher Preparation Program in the Faculty of Educational Sciences at Zarqa University in Light of Global Competitiveness from Faculty Members’ Perspective - Nashwan, Nashwan; Qdaimat, Jehad; Nashwan , Ayat (Dirasat: Educational Sciences, 2021)
This study aims to investigate the reality of student teacher preparation program in the Faculty of Educational Sciences at Zarqa University in the light of global competitiveness from the faculty members’ perspective, by defining the criteria used in the teacher preparation program. The study adopted the descriptive survey method. The study sample consisted of all the 15 faculty members working in the faculty. To achieve the objectives of the study, a questionnaire was designed consisted of (83) indicators, fulfilling (13) criteria distributed in three areas: the educational environment, the program, and the instructional effectiveness. Faculty members responded to the questionnaire on five-point Likert scale, and the results were classified according to the average responses at three levels: low, medium, and high. One of the most important results of the study is the construction of a list that includes three areas and thirteen criteria for the student-teacher preparation program in the light of global competitiveness. The researchers recommend conducting a study dealing with the learning outcomes and the graduates’ characteristics and conducting a longitudinal study to measure the development of the program. As well as, conducting similar studies in other environments.